2020
DOI: 10.1101/2020.07.24.20160101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Red blood cells injuries and hypersegmented neutrophils in COVID-19 peripheral blood film

Abstract: In the current investigation, peripheral blood films of 15 COVID-19 patients (44.78±16.55 years), proven by computed tomographic imaging and RT-PCR for coronavirus SARS-CoV-2, were analyzed at the moment of hospital admission. Blood tests showed raised inflammatory markers (C-reactive protein 58.2±61.2 mg/L) with normal values for hemoglobin (126.2±2.6 g/L), WBC (6.8±18.74 109/L) RBC (4.55±0.99 1012/L) platelets (262.4±41.8, 109/L) MCV (79.84±8.2 fL) MCH (28±3.31 pg) and MCHC (350.3±1.15 g/L). The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
3
9
1
Order By: Relevance
“…Similar red blood cell changes have been described in peripheral blood of COVID-19 patients (Lakhdari et al, 2020). Rouleaux formation is observed in 1/3 of COVID-19 patients, whereas spherocytes and echinocytes have been observed at variable levels.…”
Section: Effects On the Bloodsupporting
confidence: 78%
“…Similar red blood cell changes have been described in peripheral blood of COVID-19 patients (Lakhdari et al, 2020). Rouleaux formation is observed in 1/3 of COVID-19 patients, whereas spherocytes and echinocytes have been observed at variable levels.…”
Section: Effects On the Bloodsupporting
confidence: 78%
“…The interlaced attachments of RBCs with SARS-CoV-2 virions as observed in vitro in the hemadsorption assay [ 35 ] may well define the mechanism by which clumps (rouleaux) of RBCs form in the blood of COVID-19 patients [ 112 , 113 , 114 ], as shown in Figure 2 . These clumps would present vascular obstructive potential, given that an RBC of average disk diameter 8 µm [ 115 , 116 ] traverses through an alveolar capillary of smaller average cross-sectional diameter [ 117 ], achieved only by a distortion of the RBC’s shape to press against the capillary wall [ 116 , 118 ].…”
Section: Properties Of Sars-cov-2 Related To Its Array Of Spike Glyco...mentioning
confidence: 99%
“… Images of RBC rouleaux (clumps) from the blood of COVID-19 patients, obtained using light (( A ) [ 112 ], ( B ) [ 113 ]) and electron microscopy (( C ) [ 114 ]). The first study ( A ) found huge rouleaux formation by RBCs in 85% of COVID-19 patients studied [ 112 ]; the second ( B ) found these in 33% of patients [ 113 ]; and the third ( C ) found these prevalent in its series of 31 patients, all with mild COVID-19 [ 114 ]. Reproduced with permission from ( A ) SIMTIPRO Srl; ( B ) CC-BY 4.0; ( C ) Georg Thieme Verlag KG.…”
Section: Figurementioning
confidence: 99%
“…Salib et al reported hypersegmented neutrophils in 88% of the COVID‐19 patients while Lakhdari N et al reported them in 66.66% of the COVID‐19 patients. 20 , 21 Previous studies have reported hypersegmented neutrophils in cases of acute respiratory distress syndrome, inflammation, and severe viral respiratory infection. 22 , 23 Since, the control group in the current study was of ICU settings therefore no significant difference was noted between the two groups.…”
Section: Discussionmentioning
confidence: 99%